(untitled) (World Bulletin of Public Health, 2024)
Chest symptoms are one of the most common reasons pediatric patients present for clinical evaluation. Imaging plays a critical role in elucidating differential considerations, provides valuable information in assessing the extent of disease and associated abnormalities, influences patient management decisions, and provides a detailed assessment of response to treatment. Given the wide range of pathologies that affect the pediatric chest, anatomic localization is a useful approach to classification and can be considered in a three-component model including primary lung parenchymal processes, large airway abnormalities, and pathology arising in the mediastinum. This practical approach can be applied to some of the most commonly encountered pediatric chest pathologies. This article also reviews the advantages and limitations of current imaging techniques and characteristic imaging findings of pediatric thoracic disorders encountered in daily clinical practice.